Pemanfaatan Media Sosial Youtube sebagai Media Edukasi di Kalangan Milenial - Hasibuan, Dinda R. A.; Kartini, Kartini; Angginami, Hannum; Ritonga, Imam Hardani; Al-Rasyid , Rahmat (MES Bogor, 2023)
How the use of YouTube social media as an educational medium among millennials is the topic of this research. This study seeks to find out how the millennial generation uses YouTube as an educational medium. This study uses a descriptive approach and literature study using books and journals as a source of information. Students strongly support the use of YouTube as a learning tool, according to the findings of this study. It is easy to get more in-depth information compared to other learning resources. It is difficult to use YouTube as a source of information . Learning resources due to lack of tools and facilities, unstable internet connection. Keywords: millennial, social media, education